The Art of Hernia Surgery A Step-by-Step Guide (Springer International Publishing, 2018)
This book is a comprehensive guide to the surgical repair of inguinal and abdominal wall hernias that not only describes all potential approaches, but also places them in the context of the anatomy of the region, the pathology, and the advances in scientific knowledge over the past decade. It documents in detail the individual techniques applicable in each region (inguinal, femoral, and ventral), highlighting tips and tricks and focusing on indications, potential complications, and outcomes. In addition it presents cases of incisional hernia and examines less frequent and rare cases and complex situations. Written for surgeons from around the globe, it includes procedures used in wealthy, developed countries and those without mesh more commonly employed in developing countries. With a format designed to facilitate use in daily practice, it is invaluable for residents seeking step-by-step guidance on procedures ranging from repair of simple inguinal hernias to complex reconstruction; for general surgeons who frequently perform hernia repairs; and for hernia specialists aiming to achieve optimal results. It also appeals to researchers with an interest in the scientific background to hernia surgery.